2014
DOI: 10.1016/j.ijdevneu.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

IUGR disrupts the PPARγ‐Setd8‐H4K20me1 and Wnt signaling pathways in the juvenile rat hippocampus

Abstract: Intrauterine growth restriction (IUGR) programs neurodevelopmental impairment and long-term neurological morbidities. Neurological morbidities in IUGR infants are correlated with changes hippocampal volume. We previously demonstrated that IUGR alters hippocampal cellular composition in both neonatal and juvenile rat pups in association with altered hippocampal gene expression and epigenetic determinants. PPARγ signaling is important for neurodevelopment as well as epigenetic integrity in the brain via the PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 54 publications
1
21
0
1
Order By: Relevance
“…Consistent with our results, multiple experiments indicated that changed expression level of SETD8 may affect insulinoma cell proliferation (62), hyperglycemic memory (63), and lipid metabolism (64). One study has shown that reducing the expression levels of SETD8 may contribute to altered hippocampal cellular composition, impaired neurodevelopment, and subsequent neurocognitive impairment (65), which are associated with the phenotype of SCZ. GATAD2A is a subunit of the nucleosome remodeling and histone deacetylase (NuRD) complex, which is generally a s s o c i a t e d w i t h e m b r y o n i c d e v e l o p m e n t , c e l l u l a r differentiation, and the repression of transcription (66).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with our results, multiple experiments indicated that changed expression level of SETD8 may affect insulinoma cell proliferation (62), hyperglycemic memory (63), and lipid metabolism (64). One study has shown that reducing the expression levels of SETD8 may contribute to altered hippocampal cellular composition, impaired neurodevelopment, and subsequent neurocognitive impairment (65), which are associated with the phenotype of SCZ. GATAD2A is a subunit of the nucleosome remodeling and histone deacetylase (NuRD) complex, which is generally a s s o c i a t e d w i t h e m b r y o n i c d e v e l o p m e n t , c e l l u l a r differentiation, and the repression of transcription (66).…”
Section: Discussionsupporting
confidence: 88%
“…We next set out to assess whether the expression changes of SETD8 in response to senescence could be attributed to transcriptional regulation. In this regard, we tested possible involvement of two transcription factors, c‐MYC and PPARγ, which were previously demonstrated to mediate the expression of SETD8 (Wakabayashi et al ., ; Driskell et al ., ; Ke et al ., ). These two factors were chosen also due to their presumed roles in the senescence of various cancer cell lines (Wu et al ., ; Briganti et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…One final consideration when interpreting our data is the effect of IUGR on brain volume or cell density within a given region. Several groups have reported structural brain changes in IUGR that might affect the neurochemical profile for a given region (3,5658). However, if the changes we observed in this study were due to a reduced brain volume or cell density alone, we would have expected a uniform reduction in neurochemical profiles in all 3 IUGR brain regions.…”
Section: Discussionmentioning
confidence: 99%